Simulation of cold spray coating for powder pre-heat and impact velocity. (2021) - Khan, Mohsin; Zunaid, Mohammad; Murtaza, Qasim
Abstract: In the present work, Computational Fluid Dynamics (CFD) simulation was carried out to comprehend the role of varying pressure and gas mixture. The simulation results gave the pre-heat temperature and impact velocity of feedstock powder particles in cold spray (CS) coating process technology. The simulation was carried out using Fluent and the geometry has been drawn using SolidWorks. The pressure-based, standard k-ɛ two-equation model was used in the present simulation work. The results come out with the best-suited pressure of 7 MPa to attain high impact velocity and the pre-heat temperature. The best possible gas or gas mixture that comes out for attaining the maximum impact velocity was pure helium. The gas mixture with 80% N2 & 20% He gives the maximum pre-heat temperature. The high impact velocity improves the coating properties and pre-heating of the particles improves the bonding strength and first layer deposition in the cold spray coating process. The presence of helium gas in low concentration improves the pre-heat temperature, with high concentration tremendously improves the impact velocity of feedstock powder particles.